2005
DOI: 10.1021/jf052047f
|View full text |Cite
|
Sign up to set email alerts
|

Lupane-Type Saponins from Leaves of Acanthopanax sessiliflorus and Their Inhibitory Activity on Pancreatic Lipase

Abstract: Three known saponins, chiisanoside, 11-deoxyisochiisanoside, and isochiisanoside, and one novel saponin, 3,4-seco-4(23),20(29)-lupadiene-3,28-dioic acid 28-O-alpha-l-rhamnopyranosyl (1-->4)-beta-d-glucopyranosyl (1-->6)-beta-d-glucopyranoside, referred to as sessiloside, were isolated from a hot water extract of Acanthopanax sessiliflorus leaves. All of these saponins were lupane-type triterpene triglycosides, and their concentrations were 4.1, 1.0, 0.5, and 0.4% (w/w) of the total extract, respectively. Sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 24 publications
(41 reference statements)
5
66
0
Order By: Relevance
“…In vitro studies have shown that both sessiloside and chiisanoside inhibit HPL activity in a dosedependent manner, with IC 50 values of 0.36 and 0.75 mg/mL, respectively. 53 In mice, simultaneous administration of oil and chiisanoside (100 and 300 mg/kg) decreased plasma TG levels and increased the amount of undigested TG in the intestinal lumen. 66 No clinical data are available on A. sessiliflorus.…”
Section: Acanthopanax Sessiliflorus Sessiloside and Chiisanosidementioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have shown that both sessiloside and chiisanoside inhibit HPL activity in a dosedependent manner, with IC 50 values of 0.36 and 0.75 mg/mL, respectively. 53 In mice, simultaneous administration of oil and chiisanoside (100 and 300 mg/kg) decreased plasma TG levels and increased the amount of undigested TG in the intestinal lumen. 66 No clinical data are available on A. sessiliflorus.…”
Section: Acanthopanax Sessiliflorus Sessiloside and Chiisanosidementioning
confidence: 99%
“…51 Certain saponins such as oleanane, lupine and dammarane-type can inhibit pancreatic lipase activity and therefore have potential as treatments that could prove effective for obesity and related disorders. [52][53][54] However, the clinical potential of saponins remains difficult to judge with such limited clinical data available.…”
Section: Saponinsmentioning
confidence: 99%
“…1) Chiisanoside, 1-hydroxy-3, 4-seco-4 (23), 20 (29)-lupadien-3, 11-olid-28-oic acid 28-O--L-rhamnopyranosyl (1!4)--D-glucopyranosyl (1!6)--D-glucopyranoside, is the main component of A. sessiliflorus leaves. In our previous study, 2) we have reported that chiisanoside inhibited pancreatic lipase activity in a dose-dependent manner in vitro. Furthermore, the addition of the saponin-rich fraction (SF) of A. sessiliflorus containing chiisanoside at 42.6% (w/w) was shown to suppress the increase of body weight gain in mice when added to a high-fat diet for 4 weeks of feeding.…”
mentioning
confidence: 79%
“…Triterpenoids extracted from the fruits of A. sessiliflorus reduced nitric oxide production in macrophages . The water extracts of A. sessiliflorus inhibited pancreatic lipase activity and suppressed body weight gain in high-fat diet mice (Yoshizumi et al, 2006).…”
Section: Introductionmentioning
confidence: 92%
“…Triterpenoids extracted from the fruits of A. sessiliflorus reduced nitric oxide production in macrophages . The water extracts of A. sessiliflorus inhibited pancreatic lipase activity and suppressed body weight gain in high-fat diet mice (Yoshizumi et al, 2006).Recent studies also reports anti-oxidant and anti-aging activity of Acanthopanax species. The extracts from A. sessiliflorus leaves significantly decreased DNA and cell damage induced by oxidative stress (Ryu et al, 2012).…”
mentioning
confidence: 91%